Photocurable low-dielectric polyimide via acrylate side-chain engineering for 3D-printed RF applications - Subin Jo; Seyeon Park; Gwajeong Jeong; Bo-Young Kim; Yongchan Jang; Ji-Hun Seo; Seong-Dae Park; Sungjoon Lim; Hyunseung Yang (Chemical Engineering Journal, 2026)

Associations between environmental metal mixture exposure and urinary DNA adduct biomarkers of oxidative and alkylative damage in adults - Jang-Hun Jeong; Bo-Ri Kim; Jeong-Kyu Ji; Hyemi Lee; Kyung-Hwa Choi; Yong Min Cho; Woo Jin Kim; Young-Seoub Hong; Heon Kim; Yong-Dae Kim; Sang-Yong Eom (Environmental Research, 2026)

Hybrid carbon framework of graphitic carbon and bamboo-like CNTs for stable lithium-metal anodes - SungJu Kim; Jae Hun Choi; Dae Soo Jung; Yun Chan Kang (Chemical Engineering Journal, 2026)

Development of an integrated physiologically based toxicokinetic-toxicodynamic model for quantitative prediction of polyhexamethylene guanidine-induced human toxicity - Ji-Hun Jang; Dae-Han Park; Jong-Jin Kim; Yong Joo Park; Kyu Hyuck Chung; Hye-Jin Kim; Haewon Kim; Seung-Hyun Jeong (Archives of Toxicology, 2026)

Dual-Drug Stent with Sirolimus and WKYMVm Promotes Endothelialization and Limits Hyperplasia - Yu Jeong Jin; Dae Sung Park; Myung Ho Jeong; Doo Sun Sim; Mi Hyang Na; Chan Woo Kim; Jeong Ha Kim; Hae Jin Kee; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2026)

Pilot-scale assessment of slag reactors for manganese removal from mine drainage - Dae-Gyu Im; Duk-Min Kim; Hye-Lim Kwon; Joon-Hak Lee; Oh-Hun Kwon; Seong-Taek Yun (Environmental Geochemistry and Health, 2026)

Phylogenetic Position of the Morphologically Ambiguous Genus Leiochrides (Annelida: Capitellidae) Revealed by Its First Complete Mitogenome - Dae-Hun Kim; Junsang Youn; Junil Ko; Hyeryeong Oh; Haelim Kil; Seong-il Eyun; Man-Ki Jeong (Journal of Marine Science and Engineering, 2026)
The family Capitellidae performs critical roles in bioturbation and sediment remediation within global marine benthic ecosystems. However, they are a taxonomically challenging group due to their simple morphology and a ‘morphological mosaic’, where traditional classificatory traits, such as thoracic chaetiger counts, appear convergently across genera. Previous multi-locus studies (using 18S, 28S, H3, and COI) first highlighted this conflict, revealing the polyphyly of major genera like Notomastus and even Leiochrides itself (based on unidentified specimens). More recently, mitogenomic studies uncovered massive gene order rearrangements and a conflicting topology but did not include Leiochrides. Critically, with no complete mitogenome reported for a formally identified Leiochrides species, its true phylogenetic position and the validity of its polyphyly remain unresolved. To address this critical gap, we sequenced and characterized the first complete mitochondrial genome from a formally identified species, Leiochrides yokjidoensis, recently described from Korean waters. The complete mitogenome was 17,933 bp in length and included the typical 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), and 22 transfer RNAs (tRNAs). Gene order (GO) analysis revealed the occurrence of gene rearrangements in Capitellidae and in its sister clade, Opheliidae. A phylogenomic analysis using the amino acid sequences of 13 PCGs from 30 species established the first robust systematic position for the genus Leiochrides (based on this formally identified species). Phylogenetic results recovered Leiochrides as a sister group to the clade comprising Mediomastus, Barantolla, Heteromastus, and Notomastus hemipodus (BS 99%). This distinct placement confirms that Leiochrides represents an independent evolutionary lineage, phylogenetically separate from the polyphyletic Notomastus complex, despite their morphological similarities. Furthermore, our analysis confirmed the polyphyly of Notomastus, with N. hemipodus clustering distinctly from other Notomastus species. Additionally, signatures of positive selection were detected in ND4, and ND5 genes, suggesting potential adaptive evolution to the subtidal environment. This placement provides a critical, high-confidence anchor point for the genus Leiochrides. It provides a reliable reference to investigate the unresolved polyphyly suggested by previous multi-locus studies and provides compelling evidence for the hypothesis that thoracic chaetiger counts are of limited value for inferring phylogenetic relationships. This study provides the foundational genomic cornerstone for Leiochrides, representing an essential first step toward resolving the systematics of this taxonomically challenging family.

Critical interplay between PAF receptor and PKCδ is involved in dopaminergic insult evoked by methamphetamine in mice - Quynh Dieu Trinh; Ji Hoon Jeong; Naveen Sharma; Yen Nhi Doan Nguyen; Jung Hoon Park; Duc Toan Pham; Hoang-Yen Phi Tran; Duy-Khanh Dang; Dae-Joong Kim; Dae-Hun Park; Toshitaka Nabeshima; Hyoung-Chun Kim; et al. (Chemico-Biological Interactions, 2026)

Regulation of Autonomic Motility in Human Gastric Muscle and the Gastroepiploic Artery by Stretch and pH - Dae Hoon Kim; Seung Myoung Son; Woong Choi; Chan Hyung Kim; Hun Sik Kim; Ki Bae Kim; Wen-Xie Xu; Sang Jin Lee; Young Chul Kim; Hyo-Yung Yun (Journal of Muscle Research and Cell Motility, 2025)

Infection protective biomimetic wearable strain sensor for laryngeal and articular movement monitoring inspired by epidermal protection and dermal motion detection - Dae Yang Oh; Mun Hwan Lee; Byung Ku Jung; Hyung Jin Choi; Taesung Park; Sang Yeop Lee; Young Kyun Choi; Yoonji Yang; Awais Ali; Seongkeun Oh; Junhyeok Park; Hanseok Seo; et al. (Chemical Engineering Journal, 2025)

Exposure and health effects follow-up study of residents near a former smelter site - Young-Hun Kim; Da-Som Lee; Jung-Eum Lee; Heon Kim; Yong-Dae Kim; Young-Seoub Hong; Jung-Duck Park; Byung-Sun Choi (Toxicological Research, 2025)

Fungal-bacterial interactions leading to increased insect mortality: Trichoderma xixiacum enhances the pathogenicity of Serratia marcescens in Protaetia brevitarsis larvae - Abdelaziz Mansour; Taeho Jeong; Duyoung Lee; Jeong-Hun Song; Eunsun Kim; Dae-Weon Lee; Mohamed Mannaa; Young-Su Seo (Journal of Invertebrate Pathology, 2025)

Exposure risk assessment through toxicodynamics assessment of 4-tert-octylphenol and estimation of new reference values based on human tissue toxicity - Dae-Han Park; Ji-Hun Jang; Jong-Jin Kim; Seung-Hyun Jeong (Environmental Pollution, 2025)

The Complete Mitochondrial Genome of the Korean Endemic Polychaete Phyllodoce koreana (Lee & Jae, 1985) from Jindong Bay, Korea, with Additional Morphological and Ecological Features - Dae-Hun Kim; So Jin Ryu; Jong Rae Kim; Seong-il Eyun; Man-Ki Jeong (Journal of Marine Science and Engineering, 2025)
Phyllodoce koreana was first described in 1985 in Gwangyang Bay, a semi-enclosed bay in Korea affected by significant organic input from the Seomjin River and dredging activities near the Gwangyang Port. Since then, this Korean endemic species has received limited attention in taxonomic and ecological studies. Phyllodoce koreana is known for its resilience to mild disturbances but is vulnerable to severe environmental changes. In this study, P. koreana specimens were collected from organically polluted Asian stalked tunicate aquaculture farms at eight sites in Jindong Bay, a location with environmental conditions similar to those of Gwangyang Bay, over the course of five sampling events from March to November. Both bays experience benthic hypoxia in summer due to elevated water temperatures and organic matter accumulation. Phyllodocid specimens were primarily collected in March and November 2023, non-hypoxic periods, suggesting potential seasonal adaptations to environmental fluctuations. The morphological features of the collected specimens were consistent with the original description of P. koreana, confirming their identification. Additionally, we reported previously overlooked morphological details, contributing to a more comprehensive taxonomic understanding of the species. We also present, for the first time, the complete mitochondrial genome of this species, comprising 15,559 bp, which provides essential genetic data for future taxonomic and phylogenetic studies. The phylogenetic analysis of protein-coding genes shows that, among 17 related polychaete species, P. koreana (family Phyllodocidae) is closely related to the family Goniadidae. Future research should expand our knowledge of polychaete taxonomy by integrating additional mitochondrial genomes and investigating the role of conserved gene synteny within Polychaeta.

Efficacy and Safety Evaluation of Tacrolimus-Eluting Stent in a Porcine Coronary Artery Model - Dae Sung Park; Mi Hyang Na; Myung Ho Jeong; Doo Sun Sim; Yu Jeong Jin; Hae Jin Kee; Mun Ki Kim; Jeong Ha Kim; Young Joon Hong; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; et al. (Tissue Engineering and Regenerative Medicine, 2024)

Transcriptome sequencing of the endangered land snail Karaftohelix adamsi from the Island Ulleung: De novo assembly, annotation, valuation of fitness genes and SSR markers - Jie Eun Park; Bharat Bhusan Patnaik; Min Kyu Sang; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hongray Howrelia Patnaik; Hee Ju Hwang; So Young Park; et al. (Genes & Genomics, 2024)

Maximizing light olefin production via one-pot catalytic cracking of crude waste plastic pyrolysis oil - Xuan Tin Tran; Dae Hun Mun; Jiho Shin; Na Young Kang; Dae Sung Park; Yong-Ki Park; Jungkyu Choi; Do Kyoung Kim (Fuel, 2024)

Overview of the population genetics and connectivity of sea turtles in the East Asia Region and their conservation implications - Connie Ka Yan Ng; Takashi Ishihara; Tomoko Hamabata; Hideaki Nishizawa; Min Liu; Jia-hao Song; Tsung Hsien Li; Chia-Ling Fong; Dae Yeon Moon; Il Hun Kim (Frontiers in Marine Science, 2024)
Understanding the current status and recent development of the population genetics and connectivity of sea turtles is crucial for effective conservation management of the species. Five sea turtle species, green turtle ( Chelonia mydas ), loggerhead turtle ( Caretta caretta ), hawksbill turtle ( Eretmochelys imbricata ), olive ridley turtle ( Lepidochelys olivacea ) and leatherback turtle ( Dermochelys coriacea ), are recorded in the East Asia Region situated in the western side of the North Pacific Ocean. We compiled information from 35 published genetic studies on the five sea turtle species, with a focus on green turtle and loggerhead turtle, which are the most studied species (in 30 studies) in view of their commonness and occurrence of nesting populations. We provided an overview of the key methods and findings of these previous studies, addressing two main objectives on genetic structure of the rookeries and their differences compared to other populations, and connectivity of the rookeries and foraging aggregations. By identifying information gaps and conservation needs, we discussed future developments for sea turtle genetic studies and conservation implications in the region.

A review of the endangered mollusks transcriptome under the threatened species initiative of Korea - Hongray Howrelia Patnaik; Min Kyu Sang; Jie Eun Park; Dae Kwon Song; Jun Yang Jeong; Chan Eui Hong; Yong Tae Kim; Hyeon Jun Shin; Liu Ziwei; Hee Ju Hwang; So Young Park; Se Won Kang; et al. (Genes & Genomics, 2023)

Purification of phenoloxidase from Haliotis discus hannai and its anti-inflammatory activity in vitro - Seung-Yub Song; Dae-Hun Park; Sung-Ho Lee; Han-Kyu Lim; Jin-Woo Park; Chae-Rim Jeong; Soo-Jung Kim; Seung-Sik Cho (Fish & Shellfish Immunology, 2023)

Intensified near-field by localizing surface plasmon for enhancing photoelectrochemical responses via periodically patterned Au assemblies - Young Moon Choi; Seung Hun Roh; Eujin Kwak; Dae-Geun Choi; Seok Joon Kwon; Jung Kyu Kim; Jong Hyeok Park (Chemical Engineering Journal, 2023)

Preclinical Evaluation of an Everolimus-Eluting Bioresorbable Vascular Scaffold Via a Long-Term Rabbit Iliac Artery Model - Dae Sung Park; Myung Ho Jeong; Yu Jeong Jin; Mi Hyang Na; Doo Sun Sim; Munki Kim; Kyung Hoon Cho; Dae Young Hyun; Seok Oh; Jeong Ha Kim; Kyung Seob Lim; Jun-Kyu Park; et al. (Tissue Engineering and Regenerative Medicine, 2023)

Regulatory role of insulin-like growth factor-binding proteins in odontogenic mineralization in rats - Jung-Sun Moon; Yoo-Sung Nam; Jee-Hae Kang; Dong-Wook Yang; Dae-Yoon Kim; Su-Young Lee; Hyun-Mi Ko; Min-Seok Kim; Sun-Hun Kim (Journal of Molecular Histology, 2021)

Complete mitochondrial genome of the invasive semi-aquatic mammal, nutria Myocastor coypus (Rodentia; Myocastoridae) - Do-Hun Lee; Moo-Seung Lee; Young-Chae Kim; Il Ryong Kim; Hye Kwon Kim; Dae Gwin Jeong; Jung Ro Lee; Ji Hyung Kim (Conservation Genetics Resources, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Accuracy evaluation of the crop-weather yield predictive models of Italian ryegrass and forage rye using cross-validation - Jing-Lun Peng; Moon-Ju Kim; Mu-Hwan Jo; Doo-Hong Min; Kyung-Dae Kim; Bae-Hun Lee; Byong-Wan Kim; Kyung-Il Sung (Journal of Crop Science and Biotechnology, 2017)

Raloxifene inhibits cloned Kv4.3 channels in an estrogen receptor-independent manner - Yun Ju Chae; Dae Hun Kim; Hong Joon Lee; Ki-Wug Sung; Oh-Joo Kwon; Sang June Hahn (Pflügers Archiv - European Journal of Physiology, 2015)

Development of the Operational Oceanographic System of Korea - Kwang-Soon Park; Ki-Young Heo; Kicheon Jun; Jae-Il Kwon; Jinah Kim; Jin-Yong Choi; Kyoung-Ho Cho; Byoung-Ju Choi; Seung-Nam Seo; Young Ho Kim; Sung-Dae Kim; Chan-Su Yang; et al. (Ocean Science Journal, 2015)

B7-H4 downregulation induces mitochondrial dysfunction and enhances doxorubicin sensitivity via the cAMP/CREB/PGC1-α signaling pathway in HeLa cells - Hyoung Kyu Kim; In-Sung Song; Sun Young Lee; Seung Hun Jeong; Sung Ryul Lee; Hye Jin Heo; Vu Thi Thu; Nari Kim; Kyung Soo Ko; Byoung Doo Rhee; Dae Hun Jeong; Young Nam Kim; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Geoacoustic model at the DH-1 long-core site in the Korean continental margin of the East Sea - Woo-Hun Ryang; Yi-Kyun Kwon; Seong-Pil Kim; Dae-Choul Kim; Jin-Hyuk Choi (Geosciences Journal, 2014)

Blood levels of cadmium and lead in residents near abandoned metal mine areas in Korea - Dong-UK Park; Dae-Seon Kim; Seung-Do Yu; Kyeong-Min Lee; Seung-Hun Ryu; Soo-Geun Kim; Won-Ho Yang; Doo-Yong. Park; Yeong-Seoub Hong; Jung-Duck Park; Byung-Kook Lee; Jai-Dong Moon; et al. (Environmental Monitoring and Assessment, 2014)

Ginsenoside Re Rescues Methamphetamine-Induced Oxidative Damage, Mitochondrial Dysfunction, Microglial Activation, and Dopaminergic Degeneration by Inhibiting the Protein Kinase Cδ Gene - Eun-Joo Shin; Seung Woo Shin; Thuy-Ty Lan Nguyen; Dae Hun Park; Myung-Bok Wie; Choon-Gon Jang; Seung-Yeol Nah; Byung Wook Yang; Sung Kwon Ko; Toshitaka Nabeshima; Hyoung-Chun Kim (Molecular Neurobiology, 2014)

Genetic structure and variability of the working dog inferred from microsatellite marker analysis - Yun-Jeong Kwon; Bong-Hwan Choi; Jungwoo Eo; Choongrak Kim; Yi-Deun Jung; Ja-Rang Lee; Yuri Choi; Jeong-An Gim; Dong-Hoon Lee; Ji-Hong Ha; Dae-Soo Kim; Jae-Won Huh; et al. (Genes & Genomics, 2014)

The effects of functionalized titanium with alendronate and bone morphogenic protein-2 for improving osteoblast activity - Sung Eun Kim; Young-Pil Yun; Kyeongsoon Park; Hak-Jun Kim; Deok-Won Lee; Jung Wook Kim; Dae Hyeok Yang; Dong Hun Suh (Tissue Engineering and Regenerative Medicine, 2013)

Geoacoustic model of the transverse acoustic variability experiment area in the northern East China Sea - Woo-Hun Ryang; Seong-Pil Kim; Seongil Kim; Dae-Choul Kim (Geosciences Journal, 2013)

Non-genomic effect of glucocorticoids on cardiovascular system - Sung Ryul Lee; Hyoung Kyu Kim; Jae Boum Youm; Louise Anne Dizon; In Sung Song; Seung Hun Jeong; Dae Yun Seo; Kyoung Soo Ko; Byoung Doo Rhee; Nari Kim; Jin Han (Pflügers Archiv - European Journal of Physiology, 2012)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Biological safety and B cells activation effects of Zanthoxylum schinifolium - Dae-Hun Park; Yong-Il Park; Yong-Chun Li; Hong De Xu; Jong-Hwa Lee; Young-Jin Kim; Soon-Ae Jang; Sung Jin Park; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; Min-Jae Lee (Molecular & Cellular Toxicology, 2011)

Heavy water labeling method for measuring the effect of genistein on mammary gland carcinogenesis - Hyeon-A Kim; Kyu-Shik Jeong; Dae-Hun Park; Jeong-Ae Lee; Won-Il Jeong; Yoo Kyeong Kim (Molecular and Cellular Biochemistry, 2007)